Non-Formal Education in Bangladesh: Policy Gaps and Employment-Linked Solutions - Mosfeka , Zannat (Journal of Education and Practice, 2025)
Purpose of the Study: The primary purpose of this study is to examine the current landscape of the Non-Formal Education (NFE) system in Bangladesh by identifying key policy and implementation gaps that hinder its effectiveness. It aims to explore how these gaps impact learners’ ability to acquire market-relevant skills and access decent employment opportunities. Research Methodology: This study employed a qualitative case study approach to explore the challenges faced by students in Non-Formal Education (NFE) programs. Ten case studies were randomly selected from two NFE centers; Shikhon Kendra and Pathsala in the Kalshi slum area of Dhaka, with five students from each center. Data collection methods included face-to-face interviews, two focus group discussions with learners and practitioners, and field observations. Both open- and close-ended questionnaires were used, and tools were pre-tested for validity. Secondary data from policy documents, NGO reports, employment statistics, and academic literature supplemented the primary data. Thematic analysis was applied to organize and interpret the findings in line with the study objectives. Findings: The study identified key policy gaps limiting the effectiveness of NFE in Bangladesh, including the absence of a legal framework, inadequate funding, and poor integration with formal education. Socio-economic barriers like child labor, early marriage, and poverty further hinder participation. A strong demand exists for skill-based, inclusive, and employment-linked programs. The findings highlight the urgent need for standardized policies, curriculum reform, and greater community and labor market engagement. Unique contribution to theory, practice and policy: This study advances theoretical understanding by highlighting the complex socio-economic and structural barriers that influence the effectiveness of Non-Formal Education (NFE) in marginalized urban settings. The study offers context-specific insights from learners and educators, emphasizing the need for skill-based, flexible, and inclusive curricula aligned with current labor market demands.